Influence of Topographic Relief on Sand Transport in the Near-Surface Layer During Dust Storms in the Taklimakan Desert - Huo, Wen; Yang, Fan; Wu, Ye; Zhi, XieFei; Song, MeiQi; Zhou, ChengLong; Yang, XingHua; MamtiMin, Ali; He, Qing; Wen, Cong; Gao, JiaCheng; Meng, Lu; et al. (Frontiers in Environmental Science, 2022)
Dust storms and dust aerosols seriously affect environmental variation and climate change at regional and global scales. Accordingly, these hazards are the current focus in studies related to Earth science. The near-surface layer is an important link for the upward transmission of dust aerosols. However, the difficulty associated with obtaining real-time observation data from this layer has markedly hindered the progress of related research. In sand source areas, the topographic relief of natural dunes is easily ignored, despite serving as an essential factor affecting wind-driven dust emission, transport, and deposition. In this study, we explored the similarities and differences in horizontal dust flux (Q) between Xiaotang and Tazhong using observation data. In Xiaotang, the variation in the Q value with height was found to fit a power function; however, in Tazhong, the Q value did not show a significant gradient change. Such phenomena are caused by the secondary sand source generated by the undulation of natural dunes. The median particle diameter of the dust lifted from the ground during dust storms was essentially the same between Xiaotang and Tazhong, ranging from 74 to 82 μm in Tazhong and from 53 to 81 μm in Xiaotang. The maximum wind speed in Xiaotang was greater than that in Tazhong, resulting in a larger Q value for each particle size range in Xiaotang. The coarse sediment grain was identified as the main factor controlling the vertical variation trend of Q. Further, fine particles were found to have a minor impact.